Investigating wage bargaining power, wage inequality and industrial structure in Indonesia - Sofyan Syahnur; Marwan Marwan; Said Munzir; Hizir Hizir; Taufiq C. Dawood (Universitas Islam Indonesia, 2019)
This study investigates the bargaining power of labor over wages and the wage inequality among industries based on the industrial structure in Indonesia. It uses a panel data model and secondary data from 2008-2015. This study argues that wage inequality really matters among the industries and tends to enlarge among them despite the existence of the bargaining power of labor over wage. Findings/Originality: The labor bargaining power over wage in Large and Medium Industries still has greater probability to be increased compared to that in Small and Micro Industries. It implies that the wage inequality still matters in the labor market, particularly in the three industrial groups, and tends to enlarge among them. Government has to take care seriously on the industrial structure with regard to wage bargaining power of labor and particularly wage inequality. Moreover, the government should promote fair wage levels between industries and labor of each industrial classification, particularly in developing countries.